Moderate-high altitude training - Flores, M.; Ducharme, J. (2021)
Training at moderate to high altitude training has become increasingly familiar in exercise and continues to gain popularity among athletes and regular individuals looking to improve their endurance performance. Acclimation is the process of exposure to moderate elevations before higher altitudes intended to induce physiological adaptation during hypoxic conditions and reduce the instances of developing altitude illness (2,3,4). Today, people use these practices mainly in competitive sports to increase their endurance performanceand create advancements over their competitors(1). Mujika and other esteemed colleagues in a recent review reported the effectiveness of altitude training and associated benefits of adaptations stemmed from improved hematological responsiveness to hypoxia, exercise economy, and buffering capacity of hydrogen ions (1). Endurance performance is still compromised at higher altitudes, but acclimation helps make this less of a drastic decrement (4). While previous data have demonstrated the benefits of altitude trainingat moderate to high altitudes, there are concerns of chronic exposure to altitude and the development of pulmonary edema causing chronic arterial stiffening over time (3,4,5). Training at high altitudes places a substantial demand on the body from reduced oxygen tissue saturation and decreased efficiency for adequate gas exchange (6). To help alleviate the complication of reduced capacity for exercise during altitude training, athletes use herbal supplements to alleviatehigh altitude training dysfunction from reduced oxygen levels and improve acclimation and adaptation to hypoxic conditions (6). Specifically, ancient roots and herbs Rhodiola and Cordyceps improved endurance exercise during high-altitude training by improving time to exhaustion and improved performance (6).This is relevant because it represents a potential aid for combating concerns with altitude training. Previous research has distinguished contraindications with altitude training but has yet to conclude if sex-based differences(i.e., female/male sex hormones) impact acclimation during induced desaturation of oxygen (7). Several aspects that limit training at altitude are living at sea level, various health conditions (i.e., pulmonary/cardiac disfunction), and COVID-19 because it affects the cardiovascular system and has the potential to inflict respiratory failure and increase myocardial tissue damage (10). The purpose behind this analysis is to review scientific data that supports the benefits of altitude training, report the associated risks, potential ergogenic aids to combat concerns with altitude training,and improve acclimation/performance while finally distinguishing how to develop a safe program.